Yield and Examiner Dependence of Digital Rectal Examination in Detecting Impaction in Pediatric Functional Constipation. Issue 5 (November 2018) - Pradhan, Shikhar; Jagadisan, Barath
ABSTRACT: Objectives: Guidelines on functional constipation recommend digital rectal examination (DRE) when constipation is doubtful or with a suspicion of organic etiology. The guidelines do not clarify if DRE is mandatory to diagnose impaction. This study aims to determine the frequency of impaction detectable only on DRE among children satisfying Rome III criteria without requiring DRE and also the inter-observer influences on impaction detection by DRE. Methods: Children between 6 months to 13 years of age, presenting with history suggestive of constipation were assessed. After excluding those with suspicion of organic etiology, those who needed DRE for diagnosis of constipation and those who do not satisfy Rome III criteria without DRE, the rest who satisfied Rome III criteria were assessed for impaction by palpable fecoliths or constipation-associated fecal incontinence. Those without such impaction were randomized to 2 examiners for DRE to diagnose impaction, in the absence of contraindications. Results: Two hundred and thirty-three children were assessed. One hundred and sixty-nine satisfied Rome III without needing DRE. Forty-eight (28.4%) had impaction detectable without DRE. Among the rest, 28 (30.1%) had impaction by DRE. There was no difference between the frequency of impaction detected by the 2 examiners. Clinical characteristics were similar ( P  > 0.05) between those with impaction detectable by DRE and those without. Conclusions: DRE does detect cases of impaction not discernible by other means. Such a finding may be comparable between examiners. These children may be identified by other clinical characteristics. The clinical significance of such a finding needs more understanding from the standpoint of therapeutic choices. Abstract : Supplemental Digital Content is available in the text